การพัฒนาทักษะการแก้ปัญหาของนักศึกษาครูเคมีด้วยกิจกรรมสะเต็มศึกษาแบบสืบเสาะหาความรู้บูรณาการกระบวนการออกแบบเชิงวิศวกรรม - Poungraya, Kridsana; Nugultham, Kulthida; Wannagatesiri, Tussatrin (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2021)
Development of Chemistry Teacher Students’ Problem–Solving Skills through Inquiry–Based Learning Integrated with Engineering Design Process in STEM Activities Kridsana Poungraya, Kulthida Nugultham and Tussatrin Wannagatesiri รับบทความ: 18 มีนาคม 2564; แก้ไขบทความ: 19 กรกฎาคม 2564; ยอมรับตีพิมพ์: 9 สิงหาคม 2564; ตีพิมพ์ออนไลน์: 19 พฤศจิกายน 2564 บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อส่งเสริมทักษะการแก้ปัญหาด้วยกิจกรรมสะเต็มศึกษาแบบสืบเสาะหาความรู้บูรณาการกระบวนการออกแบบเชิงวิศวกรรมของนักศึกษาครูเคมี โดยกำหนดจุดประสงค์การวิจัยดังนี้ 1) เพื่อออกแบบกิจกรรมสะเต็มศึกษาแบบสืบเสาะหาความรู้บูรณาการกระบวนการออกแบบเชิงวิศวกรรม และ 2) เพื่อเปรียบเทียบทักษะการแก้ปัญหา ของนักศึกษาครูเคมี ก่อนและหลังการใช้กิจกรรมสะเต็มศึกษาแบบสืบเสาะหาความรู้บูรณาการกระบวนการออกแบบเชิงวิศวกรรม กลุ่มเป้าหมายเป็นนักศึกษาครูชั้นปีที่ 3 สาขาวิชาเคมี จำนวน 15 คน เครื่องมือที่ใช้ในการวิจัยประกอบด้วย 1) กิจกรรมการเรียนรู้สะเต็มแบบสืบเสาะหาความรู้บูรณาการกระบวนการออกแบบเชิงวิศวกรรมในรายวิชาการจัดการเรียนรู้วิทยาศาสตร์ และ 2) แบบประเมินทักษะการแก้ปัญหาประกอบด้วย 5 ขั้นตอน คือ การระบุปัญหา การค้นหาแนวคิดที่เกี่ยวข้อง แนวคิดในการแก้ปัญหา การออกแบบวิธีการแก้ปัญหา และการทดสอบ ปรับปรุง และประเมินผล ผลการวิจัยชี้ให้เห็นว่านักศึกษาครูเคมีมีทักษะการแก้ปัญหาหลังเรียนสูงขึ้น คำสำคัญ: ทักษะการแก้ปัญหา กระบวนการออกแบบเชิงวิศวกรรม กิจกรรมสะเต็มศึกษา Abstract This research aims to promote problem–solving skills through Inquiry–based Learning integrated with engineering design process in STEM activities of chemistry teacher students. The research objectives were set as follows: 1) to design STEM activities on inquiry–based learning integrated of engineering design process, and 2) to compare problem–solving skills of chemistry teacher students before and after receiving STEM Activities through Inquiry–based learning integrated with engineering design process. The participants were 15 third–year teacher students in chemistry major. The research instruments included 1) science learning management courses by designing a STEM activity in inquiry–based integrated engineering design process, and 2) problem solving skills assessment consisted of 5 phases, named Problem identification, related Information search, problem–solving concept, solution design, as well as testing improvement and evaluation. The results of the study indicated that the chemistry teacher students had significantly higher problem–solving skills after study. Keywords: Problem–solving skills, Engineering design process, STEM activities